Therapierefraktäre Schmerzen - Keßler, Jens; Geist, Marcus; Bardenheuer, Hubert (DMW - Deutsche Medizinische Wochenschrift, 2018)
Pain therapy concepts should be based on a biopsychosocial model. A prerequisite for adequate pain therapy is the detailed medical history. The questions about the intensity of pain and especially about the quality of pain are crucial for the selection of drug therapy. In addition to the questioning, targeted physical examination is essential. This should be repeated in case of therapy-refractory pain in the course. The transfer of clinically relevant knowledge about the emergence and the development of pain occurs in the new cross-sectional area ​​14 “pain medicine” and has been anchored in the licensing regulations. Treatment-refractory pain, despite adequate pharmacological therapy, may be the result of individual metabolism. For tumor-related pain, opioid rotation is a suitable symptom control procedure. To avoid treatment-refractory pain peaks, the medication for the need for basic medication should be adjusted in the dose. Non-drug treatment should be targeted for treatment-refractory pain to promote patient’s ownership. Physiotherapeutic measures have the goal of increasing the self-efficacy of pain and regaining confidence in one’s own bodily functions.
Keywords: therapierefraktär; Chronifizierung; biopsychosoziales Schmerzmodell; Schmerzspitzen; Opioide